An evidence-based digital prescription opioid safety toolkit for national dissemination: co-design and user testing - Waddell, Alex; Watterson, Jessica L.; Basur, Dhruv; Prawira, Christopher Owen; Picco, Louisa; Lam, Tina; Olivier, Patrick; Seguin, Joshua Paolo; Kay, Liam; Nielsen, Suzanne (Frontiers in Digital Health, 2025)
IntroductionAustralia has one of the highest rates of opioid prescribing and prescription opioid-related harm in the world. Although effective for pain relief, the use of prescription opioids is a leading cause of preventable morbidity and mortality. Barriers exist for consumers identifying their own risk factors, accessing naloxone (opioid overdose antidote) and overdose prevention education. This study aimed to co-design a digital Opioid Safety Toolkit for national dissemination through pharmacies to encourage three consumer opioid safety behaviours: (1) uptake of naloxone, (2) creating a safety plan, and (3) discussing their use of opioids, including any concerns with their healthcare professional.MethodsThe digital Toolkit was co-designed and developed using a novel approach to digital health intervention design combining the Theoretical Domains Framework (TDF) and Double-Diamond design process. Co-design involved a series of seven iterative workshops with consumers (4) and professionals (3). Workshops focused on identifying factors influencing opioid safety behaviours, exploring design preferences, sense-checking, and ideation of the user flow. User testing was conducted with the penultimate version of the Toolkit.Results13 consumers with lived experience of prescription opioid use and 14 professionals including prescribers, pharmacists, pain specialists, researchers and consumer advocates participated in up to three separate workshops. 15 consumers participated in user testing interviews. Analysis of workshops identified factors promoting safety behaviours including increased public awareness of naloxone, understanding personal risk (TDF domain of Knowledge); healthcare professional's role in education and consumers' experience of stigma (Social/professional role and identity); use of conversational aids to scaffold conversations, material resources and data ownership (Environment, context and resources). User testing elicited feedback pertaining to the information and resources on the website and the overall user interface and experience.DiscussionThe Toolkit was co-designed with consumers and professionals to facilitate opioid safety behaviours. The Toolkit includes evidence-based information, tools for risk assessment and screening, opioid use monitoring, conversation aids, and a safety plan. The Toolkit is being disseminated nationally through Australian pharmacies following a randomized controlled trial that demonstrated the Toolkit promotes safety behaviours, is easy to use and acceptable to those with lived experience of prescription opioid use and professionals.